A Population Pharmacokinetic Modeling and Simulation Study of Posaconazole Oral Suspension in Immunocompromised Pediatric Patients: A Short Communication. Issue 4 (August 2021) - Elkayal, Omar; Spriet, Isabel; Uyttebroeck, Anne; Colita, Anca; Annaert, Pieter; Allegaert, Karel; Smits, Anne; Van Daele, Ruth; Dreesen, Erwin
Abstract : Background: Posaconazole oral suspension emerged as a promising candidate for prophylaxis of invasive fungal infections in immunocompromised children. Its pharmacodynamic advantages include a broad-spectrum activity and a favorable safety profile; however, they are overshadowed by its large pharmacokinetic (PK) variability, which might cause subtherapeutic exposure. The aim of this study was to develop a population (pop) PK model based on rich sampling data to better understand the PK of posaconazole oral suspension in pediatric patients. Methods: Data were obtained from a prospective interventional study involving hospitalized pediatric patients with a hematologic malignancy and prophylactically treated with posaconazole oral suspension . After constructing the popPK model, the probability of target attainment (PTA; 100% T ≥ 0.7 mg/L) for prophylaxis under fixed, body weight-based, and body surface area-based dosing was evaluated using Monte Carlo simulation. Results: Fourteen patients contributed 112 posaconazole plasma concentrations. The PK of posaconazole was adequately described by a 1-compartment model with lag time 2.71 hours [13%]; nonlinear bioavailability ED50 99.1 mg/m 2 (fixed); first-order absorption rate constant 0.325 hour −1 [27%]; apparent volume of distribution 1150 L [34%]; and apparent clearance 15.4 L/h [24%] (∼70-kg individual). The bioavailability decreased in the presence of diarrhea and co-treatment with a proton pump inhibitor (PPI). The unexplained interindividual variability in posaconazole PK remained large. The PTA was <85%, irrespective of the simulated dosing strategy. Patients without diarrhea and not administered a PPI had the highest PTA (85% under the fixed 300-mg dosing 4 times per day). Conclusions: Therapeutic drug monitoring is recommended during prophylactic posaconazole therapy in immunocompromised pediatric patients. Large-scale comparative studies are needed to characterize the PK variability between different posaconazole formulations in this cohort.